2018
DOI: 10.1002/jso.25017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of poorly differentiated clusters and tumor budding in colorectal liver metastases

Abstract: This is the first study demonstrating PDC as a prognostic factor in CLM. TB was also a prognostic factor, but it was not an independent predictor of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
3
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 50 publications
2
36
3
14
Order By: Relevance
“…Differently from those achieved by Fonseca et al our findings indicate that PDC presence in LM, rather than PDC grade, is prognostically relevant in patients with CRC. In addition, we showed that PDC assessment in colorectal LM may be useful to predict prognosis when LM are synchronous (diagnosed prior or concurrently to primary CRC), but not metachronous.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Differently from those achieved by Fonseca et al our findings indicate that PDC presence in LM, rather than PDC grade, is prognostically relevant in patients with CRC. In addition, we showed that PDC assessment in colorectal LM may be useful to predict prognosis when LM are synchronous (diagnosed prior or concurrently to primary CRC), but not metachronous.…”
contrasting
confidence: 99%
“…We read with great interest the paper entitled “Prognostic significance of poorly differentiated clusters and tumor budding in colorectal liver metastases,” which was recently published in Journal of Surgical Oncology . In that paper, authors analyzed the prognostic relevance of a grading system based on the counting of poorly differentiated clusters (PDC)—which are aggregates of at least five neoplastic cells with no glandular formation—in colorectal liver metastases (LM).…”
mentioning
confidence: 99%
“…Tumor size and tumor marker levels are more likely to describe earlier diagnosis and are less likely to be derived from preoperative systemic treatment. Those different profiles have major prognostic effects . To better compare patients between the studied periods, we utilized PSM in order to perform a fair comparison between the two populations.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection included demographic information (age, gender, body mass index, and American Society of Anesthesiology [ASA] index) and preoperative laboratory tests (hemoglobin, platelet count, total bilirubin, albumin, international normalized ratio (INR), and carcinoembryonic antigen level). CEA was considered prior to any treatment to control liver metastases, whether chemotherapy or surgery, and the cut‐off value was set at 20 mg/dL . Oncological information was also studied: primary tumor location (right colon or left colon); primary tumor staging (T stage and lymph node status); time of diagnosis of liver metastases (up to 12 months was considered synchronous and over 12 months was considered metachronous); number of liver metastases; size of the largest liver lesion; occurrence of bilobar metastases; presence of extra‐hepatic disease; Fonǵs clinical risk score; and when employed, regimen of chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation